Culture at low glucose up-regulates mitochondrial function in pancreatic β cells with accompanying effects on viability. Issue 6 (1st November 2016) - Hals, Ingrid K.; Singh, Rinku; Ma, Zuheng; Scholz, Hanne; Björklund, Anneli; Grill, Valdemar
ABSTRACT: We tested whether exposure of β cells at reduced glucose leads to mitochondrial adaptions and whether such adaptions modulate effects of hypoxia. Rat islets, human islets and INS-1 832/13 cells were pre-cultured short term at half standard glucose concentrations (5.5 mM for rat islets and cells, 2.75 mM for human islets) without overtly negative effects on subsequently measured function (insulin secretion and cellular insulin contents) or on viability. Culture at half standard glucose upregulated complex I and tended to upregulate complex II in islets and INS-1 cells alike. An increased release of lactate dehydrogenase that followed exposure to hypoxia was attenuated in rat islets which had been pre-cultured at half standard glucose. In INS-1 cells exposure to half standard glucose attenuated hypoxia-induced effects on several viability parameters (MTT, cell number and incremental apoptotic DNA). Thus culture at reduced glucose of pancreatic islets and clonal β cells leads to mitochondrial adaptions which possibly lessen the negative impact of hypoxia on β cell viability. These findings appear relevant in the search for optimization of pre-transplant conditions in a clinical setting.